Deeper than the dead - Hoag, Tami. (Upper St. Martin's Lane, London : Orion Books Ltd., 2010)
California, 1985. Detective Tony Mendez, fresh from a law enforcement course at FBI headquarters, is charged with discovering the identity of a brutal, calculating psychopath. His search pushes him ever deeper into the lives of three children, and closer to the young teacher whose interest in recent events becomes as intense as his own.
Keywords: Women scientists -- Fiction; aSerial murder investigation -- Fiction; Fathers and sons -- Fiction